“SEJUTA BAMBU UNTUK INDONESIAKU” SOCIO-ECOPREUNEUR UNTUK MENSEJAHTERAKAN PENGRAJIN BAMBU DI DESA HARGOMULYO, GEDANGSARI, GUNUNG KIDUL, YOGYAKARTA DALAM MOMENTUM MASYARAKAT EKONOMI ASEAN( MEA) - Robist - Hidayat (LPPM Universitas Putera Batam, 2019)
Indonesia's bamboo potential is currently ranked third after India and China. Bamboo holds enormous opportunities and potential to be utilized in improving the economy. However, the potential of bamboo possessed by this nation has not been utilized optimally, this material is very important because it can be classified into a sustainable germplasm, with a note that the use is not excessive and the extraction is right. What happened in Indonesia, bamboo continued to be cut down without any effort to plant and maintain so that the number of bamboo populations continued to decline. Some areas with good potential for bamboo include Gunungkidul, Special Region of Yogyakarta. Efforts to increase the value of bamboo also need to be balanced with conservation efforts as an increase in bamboo biodiversity itself. The existence of the Asean Economic Community (AEC) at the end of 2015 is a broader economic and market integration. This indicates open competition for trade in goods, services, investment, capital and workers. From these problems, we create a socio-ecopreneur with the theme